فاعلية بيئة تعليمية قائمة على التعليم المدمج في تنمية مهارات حل المسألة الفيزيائية لدى طالبات الصف الحادي عشر بغزة - جندية، أروى صقر محمود (رابطة التربويين الفلسطينيين - قسم الأبحاث والمنشورات, 2022)
بينت الدراسة فاعلية بيئة تعليمية قائمة على التعليم المدمج في تنمية مهارات حل المسألة الفيزيائية لدى طالبات الصف الحادي عشر بغزة، باستخدام اختبار حل المسألة الفيزيائية كأداة للدراسة، على عينة مكونة من (17) طالبة من طالبات الصف الحادي عشر بمدرسة هاشم عطا الشوا الثانوية للبنات، واستخدام المنهج شبه التجريبي في تصميم المجموعة التجريبية الواحدة ذات القياس القبلي والبعدي، والمنهج الوصفي التحليلي في تحليل أسئلة الاختبار في ضوء مهارات حل المسألة الفيزيائية، حيث تراوحت نسب الكسب المعدل بلاك للاختبار ومهاراته ما بين (1.65 – 1.85)، بفروق ذات دلالة إحصائية عند مستوى دلالة (α ≤ 0.05) بين متوسطي درجات الطالبات في التطبيق القبلي والتطبيق البعدي في اختبار حل المسألة لصالح التطبيق البعدي، وفروق ذات دلالة إحصائية عند مستوى دلالة (α ≤ 0.05)بين متوسط درجات الطالبات ودرجة الإتقان لصالح متوسط درجات الطالبات. The Study showed the effectiveness of an educational environment based on blended learning in developing the physical questions skills of 11th grade students in Gaza, using the physical problem solving test as a study tool, on a sample of (17) female students of the eleventh-grade at Hashim Atta Eshawa secondary school for Girls, using the semi- experimental approach in designing a single experimental group with a pre and post measurement, and the descriptive analytical approach in analyzing the test questions based on the skills of solving the physical problem, where the average of the adjusted black gain for the test and its skills ranged between (1.65- 1.85), and statistically significant differences at the level of significance (α ≤ 0.05) between the average scores of the female students in the pre and post application of the physical question solving test, in favor of post- implementation. And statistically significant differences at the level of the significance (α ≤ 0.05) between the average scores and the degree of proficiency in favor of the average score
Keywords: التعليم الإلكتروني -- العملية التعليمية -- المهارات العلمية -- المسائل الفيزيائية -- طالبات المرحلة الثانوية